2021
DOI: 10.1177/18369391211010971
|View full text |Cite
|
Sign up to set email alerts
|

Finnish early childhood education and care leaders’ perceptions of pedagogical leadership and assessment of the implementation of the National Core Curriculum in times of change

Abstract: Finnish early childhood education and care (ECEC) experienced system-wide changes in legislation, curriculum, and teachers’ and centre leaders’ qualification requirements between 2013 and 2018. Through these changes, the Finnish ECEC follows the global trends shifting the focus of ECEC from care towards education. The data are leaders’ ( N = 41) written responses to three open-ended questions in a survey completed in 2018. The analytical framework draws on the models of educational change and human capital of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
(52 reference statements)
0
14
0
7
Order By: Relevance
“…Pedagogical leadership has emerged from the understanding that the substance of ECE determines leadership as providing the way to meet the mission and vision of the organisation (Nivala 2002). Ahtiainen, Fonsén, and Kiuru (2021) argued that leadership has altered because of several changes that the Finnish ECE system has undergone. Leading educational institutions with its curriculum, instead of social services for families, has become crucial.…”
Section: Ece and Leadership In Finlandmentioning
confidence: 99%
“…Pedagogical leadership has emerged from the understanding that the substance of ECE determines leadership as providing the way to meet the mission and vision of the organisation (Nivala 2002). Ahtiainen, Fonsén, and Kiuru (2021) argued that leadership has altered because of several changes that the Finnish ECE system has undergone. Leading educational institutions with its curriculum, instead of social services for families, has become crucial.…”
Section: Ece and Leadership In Finlandmentioning
confidence: 99%
“…More recent studies have found similar elements of pedagogical leadership exist within ECEC settings. Leading improvement has been shown to involve building collaborative understandings of policy and practice and a focus on contextual implementation (Ahtiainen et al, 2021). Other researchers have found that distributed models of pedagogical leadership involve administrative and teaching staff working interdependently towards shared goals (Heikka, 2014), developing trust through open dialogue and communication (Boe & Hognestad, 2017) and enabling educators to have ownership over pedagogical improvement (Kirk & Barblett, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other researchers have found that distributed models of pedagogical leadership involve administrative and teaching staff working interdependently towards shared goals (Heikka, 2014), developing trust through open dialogue and communication (Boe & Hognestad, 2017) and enabling educators to have ownership over pedagogical improvement (Kirk & Barblett, 2021). It has also been determined that early childhood pedagogical leaders require early childhood knowledge to interpret reforms, identify goals and lead change (Ahtiainen et al, 2021). In school contexts, however, early childhood knowledge is not always a characteristic of those who lead.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research also indicates that the director or chief executive officer of any organisation is seen as the crucial source for enabling others to demonstrate leadership. Likewise, it is expected that ECE centre directors support and encourage professional growth of their colleagues and steer the community towards sharing leadership and negotiating the meaning of distributed leadership [8,[16][17][18].…”
Section: Theoretical Framing and Literature Reviewmentioning
confidence: 99%
“…This is in part historical and, more importantly, connected with the age group of the childrenfrom birth to five or six years-attending ECE centres. One important perspective on distributed leadership is to consider it in relation to pedagogical leadership because the role of leading pedagogy within ECE centres critically impacts program quality and children's development and learning outcomes [16,19,20]. When implementing and assessing the National Core Curriculum that is the core of pedagogy, centre directors set the aims, create the working climate and support staff, but the actual implementation and assessment is done through distributing leadership [16].…”
Section: Theoretical Framing and Literature Reviewmentioning
confidence: 99%